Optimizing Ship Crew Recruitment Through the Implementation of Operational Risk Management Strategies: A Case Study of PT TOS Indonesia - Ruranha; Silvanita Mangani, Ktut; Denny Tewu, M.L. (Universitas Muhammadiyah Pontianak, 2026)
This study analyzes the optimization of ship crew recruitment through operational risk management at PT TOS Indonesia. The study is grounded in ISO 31000, HRM, and recruitment theory. A qualitative case study approach is applied using interviews, observation, and document analysis. Findings reveal key risks such as crew shortages, competency mismatches, and verification delays. Existing systems remain reactive. Therefore, risk-based strategies including standardization, digitalization, and continuous monitoring are required. The study concludes that risk-based recruitment improves effectiveness, compliance, and operational reliability. Keywords:Ship Crew Recruitment, Operational Risk Management, Manning Agency, Risk-Based Recruitment, Maritime Human Resources, ISO 31000, Recruitment Process Optimization, Maritime Safety